(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Cloud computing is one of the most powerful innovation that has caught fancy of technologists around the globe. Cloud Computing works as Pay-as-you-go” model is most appealing factor. Cloud Computing provides the capability to use computing and storage resources on a metered basis and reduce the investments in an organization’s computing infrastructure. Cloud Computing has enormous advantages such as scalability, rapid elasticity, measured services, most important of them the potential that it has for cost savings to the enterprises, it also has its share of security risks that no enterprise can afford to overlook. Security and risk assessment would encompass analysis of the impact of variety of threats and attacks on various aspects of cloud computing including Adaptation of Cloud computing, maintenance of secrecy and privacy of personal data, access and updating of data.